Money velocity in an endogenous growth business cycle with credit shocks - Szilárd Benk; Max Gillman; Michal Kejak (Cardiff University, Cardiff Business School, 2007)
The explanation of velocity in neoclassical monetary business cycle models relies on a goods productivity shocks to mimic the dataís procyclic velocity feature; money shocks are not important; and the Önancial sector plays no role. This paper sets the model within endogenous growth, adds exchange credit shocks, and Önds that money and credit shocks explain much of the velocity variation. The role of the shocks varies across sub-periods in an intuitive fashion. Endogenous growth is key to the construction of the money and credit shocks since these have similar eects on velocity, but opposite eects upon growth. The model matches the dataís average velocity and simulates most of the velocity volatility that is found in the data. Its underlying money demand is Cagan-like in its interest elasticity, so that money and credit shocks cause greater velocity variation the higher is the nominal interest rate.
Keywords: E13; E32; E44; 330; Velocity; business cycle; credit shocks; endogenous growth; Geldumlaufgeschwindigkeit; Neue Wachstumstheorie; Konjunktur; Schock; Theorie